The Effect of Procedural Rhetoric and Narrative Content in a Narrative Game-Based Fear Appeal - Hendrik Engelbrecht; Nynke van der Laan; Renske van Enschot; Emiel Krahmer; Fausto Burgemeester; Spatika Gujran; Leila Marandi (International Journal of Serious Games)
The current study evaluates the relative contributions and interaction of procedural arguments and narrative content in health interventions. Passive health interventions often fail to make health threats relevant for a young target population. While serious games have shown promise in eliciting health behaviors, the relative contribution of mechanics themselves is often hard to attribute. The current study addresses the question of whether the presence of meaningful game mechanics, in the form of procedural arguments, contributes uniquely to persuasion by heightening susceptibility and behavioral intention. Using an interactive fear-appeal the authors present the design and evaluation of a boardgame that aims to capture persuasive arguments surrounding alcohol addiction. The mechanics and narrative framing were manipulated to be able to isolate their contributions. The study supports the notion that mechanics and rules alone might not be sufficient for players to identify the content of a procedural argument, with implementation of narrative content being an important factor in making mechanics persuasive. The current study contributes to the field by being one of the few works that operationalizes the concept of procedural rhetoric, providing implications for the design of mechanics and their integration for serious games used in health behavior change.